Global Women's Work
1 online resource (422 pages)
Keywords: This volume considers how women are shaping the global economic landscape through their labor, activism, and multiple discourses about work. Bringing together an interdisciplinary group of international scholars, the book offers a gendered examination of work in the global economy and analyses the effects of the 2008 downturn on women’s labor force participation and workplace activism. The book addresses three key themes: exploitation versus opportunity; women’s agency within the context of changing economic options; and women’s negotiations and renegotiations of unpaid social reproductive labor. This uniquely interdisciplinary and comparative analysis will be crucial reading for anyone with an interest in gender and the post-crisis world.